(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This article explores the role and significance of motivation in foreign language teaching from psychological and methodological perspectives. The study examines the formation of learners’ intrinsic and extrinsic motivation and analyzes the psychological mechanisms that enhance interest in learning a foreign language. Based on major psychological theories, the paper highlights key motivational factors influencing the learning process. Special attention is given to effective pedagogical approaches, interactive methods, and innovative educational technologies that contribute to increasing learners’ motivation. The article also emphasizes the impact of motivation on the development of communicative competence, independent thinking, and overall learning effectiveness. The findings provide practical recommendations for foreign language teachers aimed at improving the quality and outcomes of the educational process.